Conquering Mount Fuji: Resolution of Tension Pneumocephalus with a Foley Urinary Catheter - Shahid M. Nimjee; Ali R. Zomorodi; D. Cory Adamson (Case Reports in Radiology)
Tension pneumocephalus is the presence of air or gas in the cranium that is under pressure. It occurs due to disruption of the skull, including trauma to the head or face, after neurosurgical procedures and occasionally, spontaneously (Schirmer et al., 2010). Patients typically present with headache but can also have neurological deficits such as decreased mental status, numbness, and weakness (Schirmer et al., 2010). It is diagnosed by computerized tomography (CT) scan (Michel, 2010). The characteristic finding is that the two frontal poles of the brain are separated by air. After diagnosis, treatment is imperative for both symptomatic relief and preventing further compression. We present a case of a patient who presented with tension pneumocephalus and unconventional treatment that resulted in clinical improvement of his symptoms and radiographic resolution of his condition.